2009
DOI: 10.1007/s10546-009-9425-z
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Mapping of Air Flow at an Urban Canyon Intersection

Abstract: In this experimental work both qualitative (flow visualisation) and quantitative (laser Doppler anemometry) methods were applied in a wind tunnel in order to describe the complex 3-dimensional flow field in a real environment (a street canyon intersection). The main aim was an examination of the mean flow, turbulence and flow pathlines characterising a complex 3-dimensional urban location. The experiments highlighted the complexity of the observed flows, particularly in the upwind region of the intersection. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 12 publications
9
52
0
1
Order By: Relevance
“…The results have been extremely useful in identifying shortcomings of current modelling approaches (Carpentieri et al, 2012) and important phenomena likely to have a major impact on flow and dispersion (Carpentieri et al, 2009;Carpentieri and Robins, 2010). However, more systematic approaches are needed to make possible the quantification and identification of the relative importance of the various parameters involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results have been extremely useful in identifying shortcomings of current modelling approaches (Carpentieri et al, 2012) and important phenomena likely to have a major impact on flow and dispersion (Carpentieri et al, 2009;Carpentieri and Robins, 2010). However, more systematic approaches are needed to make possible the quantification and identification of the relative importance of the various parameters involved.…”
Section: Discussionmentioning
confidence: 99%
“…The latter aspect (i.e. the effect of tall buildings) has been sporadically studied in the past, and previous experiments have already highlighted its importance (Carpentieri et al, 2009;Carpentieri and Robins, 2010;Heist et al, 2009;Brixey et al, 2009). However, no modelling approaches have been proposed to take account of associated flow and dispersion phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minor departures from symmetry were found to result in large differences in the exchanges. Carpentieri et al [27], making wind-tunnel measurements at an asymmetric intersection, observed complex 3D effects that enhanced the interaction of the canopy flow with the overlying flow.…”
Section: Flow and Transport At Street Scalementioning
confidence: 99%